2013
DOI: 10.1007/s00203-013-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype profiling of Rhizobium leguminosarum bv. trifolii clover nodule isolates reveal their both versatile and specialized metabolic capabilities

Abstract: Rhizobium leguminosarum bv. trifolii (Rlt) are soil bacteria inducing nodules on clover, where they fix nitrogen. Genome organization analyses of 22 Rlt clover nodule isolates showed that they contained 3–6 plasmids and majority of them possessed large (>1 Mb), chromid-like replicon with exception of four Rlt strains. The Biolog phenotypic profiling comprising utilization of C, N, P, and S sources and tolerance to osmolytes and pH revealed metabolic versatility of the Rlt strains. Statistical analyses of our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The symbiotic genes of R. leguminosarum located on the pSym plasmid were also found to be highly variable and affected efficient symbioses with several host plants (Ramirez-Bahena et al 2008 , 2009 ; Marek-Kozaczuk et al 2013 ). In this study, the genomes of the T. rubens nodule isolates were found to be highly differentiated based on the plasmid content showing considerable genetic variability as described earlier for Rlt isolated from nodules of T. pratense (Mazur et al 2011 , 2013 ). The taxonomic position of the selected T. rubens isolates was unambiguously defined as R. leguminosarum .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The symbiotic genes of R. leguminosarum located on the pSym plasmid were also found to be highly variable and affected efficient symbioses with several host plants (Ramirez-Bahena et al 2008 , 2009 ; Marek-Kozaczuk et al 2013 ). In this study, the genomes of the T. rubens nodule isolates were found to be highly differentiated based on the plasmid content showing considerable genetic variability as described earlier for Rlt isolated from nodules of T. pratense (Mazur et al 2011 , 2013 ). The taxonomic position of the selected T. rubens isolates was unambiguously defined as R. leguminosarum .…”
Section: Discussionsupporting
confidence: 64%
“…The genome of Rhizobium leguminosarum is large and complex, consisting of a chromosome and a variable number of large plasmids (Young et al 2006 ; Mazur et al 2011 ; Kumar et al 2015 ). Symbiotic functions are encoded by genes located in symbiotic plasmids (pSym) (Perret et al 2000 ; Young et al 2006 ; Mazur et al 2011 , 2013 ). The plasmids constitute a pool of accessory genetic information and contribute to the plasticity and dynamic state of the genome commonly observed among members of the Rhizobiaceae family (Palacios and Newton 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…to persist in adverse environments and compete successfully with other bacteria (Mazur et al, 2013). Therefore, the ability of legume-nodulating rhizobia to solubilise different inorganic phosphates sources, the potential to tolerate wide range of stress, and versatility in metabolism should be considered when selecting strains as biofertilizer.…”
Section: Original Researchmentioning
confidence: 99%
“…RtTA1 derivatives cured of pRleTA1b or pRleTA1d and especially deleted in pRleTA1a (in which no genes related with polysaccharide biosynthesis were previously mapped) produced slightly higher amounts of EPS in comparison to the wild type, suggesting the existence of a complex regulatory network of EPS synthesis consisting of genes located on different plasmids and especially on pSym [ 175 ]. Extrachromosomal replicons were previously shown to confer the significant metabolic versatility to bacteria, which is important for their adaptation in the soil and nodulation competitiveness [ 7 , 8 , 176 ] and may also be exerted by modulation of the rhizobial surface composition. It has been shown that the quality and quantity of surface polysaccharides, particularly exopolysaccharides (EPSs) and lipopolysaccharides (LPSs), produced by rhizobia may influence both their autoaggregation and biofilm formation [ 177 , 178 , 179 ].…”
Section: Wzx/wzy-dependent Synthesis Of Exopolysaccharide In mentioning
confidence: 99%